Method for improving stability of photoactive layer and organic photovoltaic device
Through low-voltage annealing treatment technology, the problem of poor stability of organic photovoltaic cell devices is solved, the morphology and light stability of the photoactive layer are significantly improved, the overall stability and performance of organic photovoltaic devices are improved, and it is suitable for industrial production.
Patent Information
- Application Number
- CN202411231155.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-17
AI Technical Summary
The stability of organic photovoltaic cell devices is poor, mainly affected by factors such as light, water and oxygen, heating and mechanical stress. It is difficult for the existing technology to effectively improve the morphology and light stability of the photoactive layer.
Low-pressure annealing treatment technology is used to anneale the photoactive layer to reduce its free volume. Combined with an optimized preparation method, the morphology and light stability of the photoactive layer are improved, thereby improving the stability of the overall device.
It significantly improves the stability of the photoactive layer and the comprehensive performance of organic photovoltaic devices, reduces the cost of raw materials, is suitable for industrial production, and is universal.
Smart Images

Figure CN119156094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials and photovoltaic cells, and in particular to a method for improving the stability of a photoactive layer and an organic photovoltaic device. Background Art
[0002] The substantial growth in energy demand around the world has caused serious environmental pollution and energy shortages. The extensive use of fossil fuels has exacerbated the greenhouse effect, leading to global climate deterioration and natural disasters. Based on these current situations, researchers from various countries have to focus on the development and utilization of renewable energy such as wind power, hydropower, and solar energy. As a substitute for fossil fuels, renewable energy has great potential and is also the focus of current research.
[0003] As an economically viable renewable energy source, organic photovoltaic devices are increasingly attracting widespread attention from the research community due to their unique advantages. After nearly a decade of steady development, the current maximum energy conversion efficiency of organic solar cells has exceeded 20%. Compared with inorganic silicon solar cells, the advantages of organic solar cells are more obvious, mainly reflected in: the source of raw materials is more extensive and the cost is lower, the molecular structure of the raw materials is highly modifiable, the function is adjustable, the film-forming property is good, and flexible electronic devices can be prepared. The processing technology is simple and can be prepared on a large area. Although organic solar cells have many advantages, they also have some problems. The most prominent problem is poor stability, which makes it difficult to meet commercial needs.
[0004] In the past few decades, in order to improve the competitiveness of organic photovoltaic cells and meet the market's expectations for different organic photovoltaic cell products, most research and development work has focused on designing polymer materials with novel structures and functions, and trying to achieve breakthroughs in photoelectric efficiency through ternary or stacking strategies. This has led to few people paying attention to the stability of photovoltaic cell devices. Analysis shows that the stability of photovoltaic cell devices is mainly restricted by factors such as light, water oxygen, heating, mechanical stress, and electrode diffusion. Water molecules and oxygen in the air can damage the electrodes and interface layers, causing serious chemical and physical degradation. Oxygen will react with the molecules in the photoactive layer to produce low potential well density of electrons, and ultimately seriously damage the open circuit voltage and fill factor of the device. Light can cause the polymer donor to undergo photooxidation to generate singlet oxygen, and the acceptor to undergo photolysis to generate persistent free radicals. In addition, the photoinduced degradation of the interface layer will seriously damage the molecular structure of the active layer, causing the device performance to decline rapidly. The decomposition temperature of the photoactive layer material is generally much higher than the processing temperature. Therefore, the thermal intolerance of the photoactive layer material is mainly due to the fact that the film undergoes additional heat treatment, which accelerates the process from the thermodynamically unstable metastable state to the stable state, causing excessive aggregation and crystallization of molecules, and seriously destroying the microscopic morphology.
[0005] In summary, it is urgent to seek a universal method to improve the stability of organic photovoltaic cell devices. The search found that many researchers have done a lot of exploration to improve the performance of the photoactive layer and the corresponding devices. For example, Chinese patent CN106784341A microwave annealed the perovskite active layer under inert protective gases such as nitrogen or argon, Chinese patent CN105977388B used a combination of solvent annealing and thermal annealing at room temperature and pressure to treat the active layer of polymer solar cells, Chinese patent CN114744127A used low-boiling point solvent vapor to solvent anneal the active layer of organic solar cells, and Chinese patent CN111883662B used a high-temperature rotary annealing process to treat the active layer of organic solar cells. Analysis shows that these existing technical solutions are relatively complex, and more importantly, none of them involve the dual improvement or improvement of the morphological stability and photostability of the photoactive layer. Summary of the invention
[0006] The main purpose of the present invention is to solve the poor stability problem of organic photovoltaic cell devices commonly existing in the prior art, and creatively use low-pressure annealing to treat the photoactive layer of the device to reduce its free volume, thereby improving the morphological stability and photostability of the photoactive layer, and then with the optimization of a series of preparation methods, ultimately improving the overall stability of the device. To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for improving the stability of a photoactive layer comprises: preparing a slurry using a donor material, an acceptor material and an additive, preparing a film layer using the slurry, annealing the prepared film layer in a low-pressure environment, and finally obtaining a photoactive layer film with excellent stability.
[0008] Specifically, the donor material is selected from at least one of PM6 and D18, and its chemical structure is as follows:
[0009]
[0010] Specifically, the receptor material is selected from at least one of L8-BO, IT-4F, and BTP-4Cl-C9-20, and its chemical structure is as follows:
[0011]
[0012] Specifically, the additive is DIO, and its structural chemical formula is as follows:
[0013]
[0014] Specifically, the solvent used to prepare the slurry is chloroform or chlorobenzene.
[0015] Specifically, the mass ratio of the donor material to the acceptor material in the slurry is 1:1-1.5, and the amount of the additive added is equivalent to 0.2%-0.5% of the total volume of the donor, the acceptor and the solvent.
[0016] Specifically, the concentration of the acceptor material in the slurry is 10-18 g / L.
[0017] Specifically, a film layer is prepared on a substrate by spin coating, scraping or dipping, and then the substrate is placed on a hot stage for low-pressure annealing.
[0018] Specifically, the low pressure environment is a nitrogen protective atmosphere of -100 kPa to -10000 kPa.
[0019] Specifically, the annealing temperature of the low-pressure annealing treatment is 80-150° C., and the insulation time at this temperature does not exceed 20 minutes. During operation, the hot plate is preheated to the annealing temperature before placing the substrate.
[0020] Specifically, the thickness of the prepared photoactive layer film is 70-100 nm.
[0021] At the same time, the present invention also provides a photoactive layer prepared according to the method.
[0022] As a third aspect, the present invention further provides an organic photovoltaic device comprising the above-mentioned photoactive layer, which comprises a substrate, a hole transport layer, a photoactive layer, an electron transport layer, and a metal electrode arranged in sequence.
[0023] Specifically, the substrate is a transparent conductive indium tin oxide substrate.
[0024] Specifically, the hole transport layer is MoO3, and the preparation method thereof is as follows: a hole transport layer with a thickness of 8-12 nm is formed on a substrate by mask evaporation in a high vacuum environment.
[0025] Specifically, the electron transport layer is a fullerene / BCP double-layer structure, and the thickness of the fullerene and BCP are both 8-12nm. The preparation method of the electron transport layer is as follows: first, fullerene is evaporated onto the photoactive layer through a mask in a high vacuum environment, and then BCP is evaporated onto the fullerene using the same method. The chemical structures of fullerene and BCP are shown below:
[0026]
[0027] Specifically, the metal electrode is Ag, and its thickness is 80-120 nm. The metal electrode is formed on the electron transport layer by vacuum evaporation.
[0028] The mechanism of action of the low-pressure heat treatment in the present invention mainly includes the following points: ① During the low-pressure heat treatment process, the organic molecules in the film can undergo molecular thermal motion (i.e., self-assembly), which improves the molecular order of the active layer, thereby improving the photoelectric performance of the organic solar cell. ② Low-pressure heat treatment can remove solvents and additives remaining in the photoactive layer, thereby improving the photostability of the thin film layer and the entire device. ③ Low-pressure heat treatment can also reduce the free volume of the active layer, and advance the relaxation behavior of the thin film after film formation, thereby improving the morphological stability of the active layer. In summary, low-pressure heat treatment synergistically improves the morphological stability and photostability of the active layer from multiple levels.
[0029] The present invention significantly improves the stability of the photoactive layer through low-pressure heat treatment, thereby improving the stability and comprehensive performance of the organic photovoltaic device. Compared with the existing similar technologies, this solution has the following advantages: (1) the raw material cost is low and the preparation method is simple, which is suitable for industrial development; (2) it can be used for a variety of active layer material systems and has good universality; (3) all functional layers of the organic photovoltaic device are formed by evaporation and can be prepared on a large area, which is also conducive to industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of the organic photovoltaic device prepared in Example 1.
[0031] Figure 2 Free volume diagrams obtained by in-situ ellipsometry testing of different films.
[0032] Figure 3 SPM height map of the aged morphology of D18:L8-BO film.
[0033] Figure 4 This is a scanning probe microscope height map of the aged morphology of PM6:BTP-4Cl-C9-20 film.
[0034] Figure 5 This is a scanning probe microscope height map of the aged morphology of PM6:IT-4F film.
[0035] Figure 6 This is the absorbance test characteristic curve of PM6:L8-BO film light chemical aging.
[0036] Figure 7 This is the absorbance test characteristic curve of D18:L8-BO film light chemical aging.
[0037] Figure 8 This is the life test curve of the optimized organic photovoltaic device.
[0038] Fig. 9 This is the life test curve of a conventional organic photovoltaic device. DETAILED DESCRIPTION
[0039] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.
[0040] Example 1
[0041] MoO3 was evaporated onto a transparent conductive indium tin oxide substrate through a mask in a high vacuum environment to obtain a transparent conductive indium tin oxide substrate / MoO3, wherein the thickness of the MoO3 film (ie, the hole transport layer) was 10 nm.
[0042] A transparent conductive indium tin oxide substrate / MoO3 was used as a new substrate, and a photoactive layer film with a thickness of 80 nm was prepared on its surface. Of course, the substrate here can also be replaced with an ordinary glass substrate or a silicon wafer substrate, etc., so as to facilitate the separate testing of the structure and performance of the prepared photoactive layer.
[0043] Dissolve 1g PM6 and 1.2g L8-BO in 160mL chloroform, add 0.5mL DIO and stir evenly to obtain slurry. Add the prepared slurry dropwise onto the substrate, and then spin-coat it at 2400 rpm to form a film. Transfer the substrate together with the wet film on it to a hot plate at 80°C, anneal at this temperature in a low-pressure nitrogen environment of -100kPa for 5min, and then cool naturally to room temperature to obtain a transparent conductive indium tin oxide substrate / MoO3 / photoactive layer.
[0044] Fullerene is evaporated onto the photoactive layer through a mask in a high vacuum environment, and then BCP is evaporated onto the fullerene film layer under the same conditions, wherein the thicknesses of the fullerene layer and the BCP layer are 10 nm and 10 nm, respectively.
[0045] By vacuum evaporation, a 100nm thick Ag electrode was formed on the BCP layer. Figure 1 The structure shown is an organic photovoltaic device of transparent conductive indium tin oxide substrate / MoO3 / photoactive layer / fullerene / BCP / Ag, denoted as ITO / MoO3 / PM6:L8-BO / BCP / C 60 / Ag.
[0046] Example 2
[0047] MoO3 is evaporated onto a transparent conductive indium tin oxide substrate through a mask in a high vacuum environment to obtain a transparent conductive indium tin oxide substrate / MoO3, wherein the thickness of the MoO3 film is 10 nm.
[0048] A transparent conductive indium tin oxide substrate / MoO3 was used as a substrate, and a photoactive layer film with a thickness of 80 nm was prepared on its surface. 1 g D18 and 1.2 g L8-BO were dissolved in 160 mL chloroform, and then 0.5 mL DIO was added and stirred evenly to obtain a slurry. The prepared slurry was dripped onto the substrate, and then spin-coated at a speed of 2400 rpm to form a film. The substrate and the wet film thereon were transferred to a hot stage at 80°C, and annealed at this temperature in a low-pressure nitrogen atmosphere of -100 kPa for 5 minutes, and then naturally cooled to room temperature to obtain a transparent conductive indium tin oxide substrate / MoO3 / photoactive layer.
[0049] Fullerene is evaporated onto the photoactive layer through a mask under a high vacuum environment, and then BCP is evaporated onto the fullerene film layer under the same conditions, wherein the thickness of the fullerene layer and the BCP layer are both 10 nm.
[0050] A 100 nm thick Ag electrode was formed on the BCP layer by vacuum evaporation, thereby constructing an organic photovoltaic device with a structure of transparent conductive indium tin oxide substrate / MoO3 / photoactive layer / fullerene / BCP / Ag, denoted as ITO / MoO3 / D18:L8-BO / BCP / C 60 / Ag.
[0051] Example 3
[0052] MoO3 is evaporated onto a transparent conductive indium tin oxide substrate through a mask in a high vacuum environment to obtain a transparent conductive indium tin oxide substrate / MoO3, wherein the thickness of the MoO3 film is 10 nm.
[0053] A transparent conductive indium tin oxide substrate / MoO3 was used as a substrate, and a photoactive layer film with a thickness of 80 nm was prepared on its surface. 1g PM6 and 1g IT-4F were dissolved in 143mL chloroform, and then 0.7mL DIO was added and stirred evenly to obtain a slurry. The prepared slurry was dripped onto the substrate, and then spin-coated at a speed of 2400 rpm to form a film. The substrate and the wet film thereon were transferred to a hot stage at 100°C, and annealed at this temperature in a low-pressure nitrogen environment of -100kPa for 5 minutes, and then naturally cooled to room temperature to obtain a transparent conductive indium tin oxide substrate / MoO3 / photoactive layer.
[0054] Fullerene is evaporated onto the photoactive layer through a mask under a high vacuum environment, and then BCP is evaporated onto the fullerene film layer under the same conditions, wherein the thickness of the fullerene layer and the BCP layer are both 10 nm.
[0055] A 100 nm thick Ag electrode was formed on the BCP layer by vacuum evaporation, thereby constructing an organic photovoltaic device with a structure of transparent conductive indium tin oxide substrate / MoO3 / photoactive layer / fullerene / BCP / Ag, denoted as ITO / MoO3 / PM6:IT-4F / BCP / C. 60 / Ag.
[0056] Example 4
[0057] MoO3 is evaporated onto a transparent conductive indium tin oxide substrate through a mask in a high vacuum environment to obtain a transparent conductive indium tin oxide substrate / MoO3, wherein the thickness of the MoO3 film is 10 nm.
[0058] A transparent conductive indium tin oxide substrate / MoO3 was used as a substrate, and a photoactive layer film with a thickness of 80 nm was prepared on its surface. 1g PM6 and 1.2g BTP-4Cl-C9-20 were dissolved in 160mL chloroform, and then 0.5mL DIO was added and stirred evenly to obtain a slurry. The prepared slurry was dripped onto the substrate, and then spin-coated at a speed of 2400 rpm to form a film. The prepared slurry was dripped onto a hot stage at 80°C, and annealed at this temperature in a low-pressure nitrogen environment of -100kPa for 5 minutes, and then naturally cooled to room temperature to obtain a transparent conductive indium tin oxide substrate / MoO3 / photoactive layer.
[0059] Fullerene is evaporated onto the photoactive layer through a mask under a high vacuum environment, and then BCP is evaporated onto the fullerene film layer under the same conditions, wherein the thickness of the fullerene layer and the BCP layer are both 10 nm.
[0060] A 100 nm thick Ag electrode was formed on the BCP layer by vacuum evaporation, thereby constructing an organic photovoltaic device with a structure of transparent conductive indium tin oxide substrate / MoO3 / photoactive layer / fullerene / BCP / Ag, denoted as ITO / MoO3 / PM6:BTP-4Cl-C9-20 / BCP / C 60 / Ag.
[0061] Comparative Example 1
[0062] PEDOT:PSS and deionized water were mixed evenly at a volume ratio of 1:1 to obtain diluted PEDOT:PSS. The diluted PEDOT:PSS was spin-coated onto a transparent conductive indium tin oxide substrate at a speed of 5000 rpm in an air environment to obtain a transparent conductive indium tin oxide substrate / PEDOT:DSS, wherein the thickness of the PEDOT:DSS film (i.e., the hole transport layer) was about 10 nm.
[0063] A transparent conductive indium tin oxide substrate / PEDOT:DSS was used as a substrate, and a photoactive layer film with a thickness of 80 nm was prepared on its surface. 1g PM6 and 1.2g L8-BO were dissolved in 160mL chloroform, and 0.5mL DIO was added and stirred evenly to obtain a slurry. The prepared slurry was dripped onto the substrate, and then spin-coated at a speed of 2400 rpm to form a film. The substrate and the wet film thereon were transferred to a hot stage at 80°C, and annealed at this temperature in a low-pressure nitrogen environment of -100kPa for 5 minutes, and then naturally cooled to room temperature to obtain a transparent conductive indium tin oxide substrate / PEDOT:PSS / photoactive layer.
[0064] 1 g of PDINN was dissolved in 1 mL of methanol solvent and stirred evenly to obtain an electron transport layer slurry. The electron transport layer slurry was spin-coated onto the surface of the photoactive layer under nitrogen protection at a spin coating speed of 3000 rpm to obtain a transparent conductive indium tin oxide substrate / PEDOT:PSS / photoactive layer / PDINN, wherein the thickness of the PDINN film was 10 nm.
[0065] A 100 nm thick Ag electrode was formed on the PDINN film layer by vacuum evaporation, thereby constructing an organic photovoltaic device with a structure of transparent conductive indium tin oxide substrate / PEDOT:PSS / photoactive layer / PDINN / Ag, denoted as ITO / PEDOT:PSS / PM6:L8-BO / PDI NN / Ag.
[0066] In order to fully understand the performance of the photoactive layers and organic photovoltaic devices prepared in various embodiments and comparative examples of the present invention, samples were taken and the following tests were performed:
[0067] (1) Structural relaxation test
[0068] Test method: The sample to be tested is heated to 150°C (near the glass transition temperature of the material system) at a heating rate of 25°C / min and kept at a constant temperature. During this period, the film thickness is continuously monitored using an in-situ ellipsometer. The reduced film thickness during the entire heating process is the free volume of the sample to be tested. In order to eliminate the error of a single sample, three samples are set in each group, which are recorded as sample1#, sample2#, and sample3#.
[0069] Preparation method of low-pressure thermal annealing sample: Referring to the preparation method in Example 1, a photoactive layer is prepared on a silicon wafer substrate using a slurry. 1g PM6 and 1.2g L8-BO are dissolved in 160mL chloroform, and then 0.5mL DIO is added and stirred evenly to obtain a slurry; the prepared slurry is dripped onto the silicon wafer substrate, and then spin-coated at a speed of 2400 rpm to form a film. The silicon wafer substrate together with the wet film thereon is transferred to a hot stage at 80°C, and annealed at this temperature in a low-pressure nitrogen environment of -100kPa for 5 minutes, and then naturally cooled to room temperature to obtain a low-pressure thermal annealing sample.
[0070] Preparation method of untreated group samples: 1g PM6 and 1.2g L8-BO were dissolved in 160mL chloroform, and then 0.5mL DIO was added and stirred evenly to obtain a slurry, the prepared slurry was dropped onto a silicon wafer substrate, and then spin-coated at a speed of 2400 rpm to form a film to obtain an untreated group sample.
[0071] The structural relaxation test results are as follows: Figure 2 As shown. As can be seen from the figure, the photoactive layer film of the untreated group showed an obvious inflection point in the 2nd-3rd minute of the heating process. At this time, the temperature was about 65°C, corresponding to the boiling point of the chloroform solvent. This shows that there is residual unvolatile solvent in the untreated photoactive layer film; while the photoactive layer film of the low-pressure thermal annealing group had no inflection point at this stage, indicating that there was no residual solvent. When the temperature rises to 150°C, the molecules in the photoactive layer film relax, and the greater the free volume in the film, the greater the decrease in film thickness. Based on this, it was measured that the film thickness of the untreated group decreased by about 1.59%, and the film thickness of the low-pressure heat treatment group decreased by about 0.98%. This shows that low-pressure heat treatment can indeed significantly reduce the free volume of the photoactive layer, thereby reducing the molecular motion space of the photoactive layer, and ultimately improving the stability of the photoactive layer.
[0072] (2) Scanning probe microscopy test
[0073] Test method: Place the sample on a hot table and observe it with a scanning probe microscope. Then heat the sample to 80°C, keep it at this temperature for 24 hours, and observe it again with a scanning probe microscope. The results are as follows: Figure 3-5 shown.
[0074] Referring to the preparation methods of the above-mentioned low-pressure thermal annealing group and the untreated group and Examples 2-4, a series of different photoactive layer films were prepared on silicon wafer substrates, among which D18:L8-BO, PM6:IT-4F, and PM6:BTP-4Cl-C9-20 correspond to the photoactive layer film formulas and preparation methods in Example 2, Example 3, and Example 4, respectively.
[0075] As can be seen from the figure, the samples in the untreated group have a large change in morphology after thermal aging, and the roughness is significantly improved; while the samples in the low-pressure heat treatment group have a small change in morphology after aging, and the change in roughness is even smaller. This comparison result shows that the samples obtained by low-pressure heat treatment have better morphological stability.
[0076] (3) Absorbency test
[0077] Test method: Use an absorbance tester to test the absorbance of the glass substrate in advance, then test the absorbance of the photoactive layer film sample made using the glass substrate, then take out the photoactive layer film sample and place it under an ultraviolet light source for 24 hours, and test its absorbance again. The results are as follows: Figure 6-7 shown.
[0078] Referring to the preparation methods of the above-mentioned low-pressure thermal annealing group and the untreated group and Examples 1-2, a series of different photoactive layer films were prepared on silicon wafer substrates, wherein PM6:L8-BO and D18-L8-BO correspond to the photoactive layer film formulas and preparation methods in Examples 1 and 2, respectively.
[0079] As can be seen from the figure, the decrease in absorbance of the samples in the low-pressure heat treatment group after UV aging is significantly lower than that of the samples in the untreated group, indicating that the low-pressure heat treatment improves the photostability of the active layer film.
[0080] (4) Life test
[0081] The life test was carried out using the two organic photovoltaic devices prepared in Example 1 and Comparative Example 1 (corresponding to the optimized device and the conventional device, respectively) as test samples. The specific test method is: placing the organic photovoltaic device sample in the groove of the stability tester, and then using the stability tester to continuously monitor the photoelectric performance of the device, wherein the test environment temperature is 25°C, the light source is LED white light, and the ambient atmosphere is air. The test results are as follows: Figure 8-9 shown.
[0082] As can be seen from the figure, compared with the untreated device, the photoelectric conversion efficiency of the low-pressure heat-treated device decreases more slowly and has better operating stability.
Claims
1. A method for improving the stability of a photoactive layer, characterized in that The method comprises: preparing slurry with donor material, acceptor material and additive as raw materials, preparing film layer with the slurry, and annealing the prepared film layer in a low-pressure environment to obtain a stable photoactive layer film.
2. The method according to claim 1, characterized in that: The donor material is selected from at least one of PM6 and D18, the acceptor material is selected from at least one of L8-BO, IT-4F, and BTP-4Cl-C9-20, the additive is DIO, and the solvent used to prepare the slurry is chloroform or chlorobenzene.
3. The method according to claim 1, characterized in that: The mass ratio of the donor material to the acceptor material in the slurry is 1:1-1.5, and the amount of the additive added is equivalent to 0.2%-0.5% of the total volume of the donor, the acceptor and the solvent.
4. The method according to claim 1, characterized in that: The film layer is prepared on the substrate by spin coating, blade coating or dipping, and then the substrate is placed on a hot stage for low-pressure annealing.
5. The method according to claim 4, characterized in that: The low pressure environment is specifically a nitrogen protective atmosphere of -100 kPa to -10000 kPa.
6. The method according to claim 4, characterized in that: The annealing temperature is 80-150°C, and the holding time does not exceed 20 minutes. During operation, preheat the hot plate to the annealing temperature before placing the substrate.
7. A photoactive layer having good morphological stability and photostability, characterized in that: The photoactive layer is prepared according to any one of the methods of claims 1-6, and has a thickness of 70-100 nm.
8. An organic photovoltaic device based on the photoactive layer according to claim 7, characterized in that: The organic photovoltaic device comprises a substrate, a hole transport layer, a photoactive layer, an electron transport layer and a metal electrode which are arranged in sequence.
9. The organic photovoltaic device according to claim 8, characterized in that: The substrate is specifically a transparent conductive indium tin oxide substrate, the hole transport layer is specifically MoO3, the electron transport layer is a fullerene / BCP double-layer structure and the fullerene is close to the hole transport layer, and the metal electrode is specifically Ag.
10. The organic photovoltaic device according to claim 9, characterized in that: The thickness of the hole transport layer is 8-12 nm, the thickness of the fullerene and BCP in the electron transport layer is 8-12 nm, and the thickness of the metal electrode is 80-120 nm.
